Effectiveness Test Of Face Wash Gel Kersen Leaf (Muntingia Calabura) Thick Extract As Anti-Acne Agent - Adi Yuhara, Novena (Jurnal EduHealth, 2024)
Acne Vulgaris or acne is a skin disease caused by a blockage in the pores of the skin that causes oil secretion to be inhibited which will increasingly enlarge and experience inflammation and bacterial activity. One of the bacteria that can trigger acne is Stapyloccus aureus. Kersen plant is one of the plants that have properties as antibacterial. face wash gel is a facial cleanser with a gel base that contains foam, usually used for sensitive, oily and acne skin. Investigating the antibacterial properties of the Kersen plant may offer a potential treatment strategy. Additionally, the physical tests of gel-based face washe warrant further exploration. The purpose of this study was to see the effect of carbopol on the preparation and also to see the concentration of kersen leaf extract that can inhibit S.aureus bacteria. Preparation was done by dissolving kersen leaf extract with ethanol. Then in a separate place, Carbopol was developed with warm water (40-50°C) until it expanded. Then in a glass beaker dissolved propyl paraben, methyl paraben and SLS with distilled water and added Carbopol that has expanded stir until homogeneous and formed a gel base. Then Kersen leaf extract was added and stirred until homogeneous and TEA was added little by little along with stirring until homogeneous. Physical tests were carried out including organoleptic tests by observing the aroma, color and shape, testing the pH of the preparation with universal pH paper, testing the foam height of the preparation, testing the viscosity with a Brookfield viscometer, testing homogeneity and conducting bacterial activity tests with the paper disk method. The results obtained by the preparation of face wash gel of kersen leaf extract with F0-F2 obtained preparations that have a cloudy, light brown and dark brown color. It has a kersen smell with the addition of kersen and its texture from liquid to thick. The preparation has a pH of 7 and is homogeneous, has a viscosity that meet the requirements. The foam height of the preparation is in the range of 8.9 cm - 9.2 cm, which meets the requirements. In the activity test results, it was found that F2 with an extract concentration of 0.5 g had a better inhibition zone of 60 mm.